2021
DOI: 10.1186/s12967-021-03136-2
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib protects T cells in patients with CLL from proliferation-induced senescence

Abstract: Background The development of Bruton’s tyrosine kinase inhibitors (BTKi) for the treatment of chronic lymphocytic leukaemia (CLL) has provided a highly effective and relatively non-toxic alternative to conventional chemotherapy. Some studies have shown that BTKi can also lead to improvements in T cell immunity in patients despite in vitro analyses suggesting an immunosuppressive effect of BTKi on T cell function. Methods In this study, we examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
4
14
0
Order By: Relevance
“…While this may account for some observed toxicities, these changes may also play a role in therapeutic activity. Inhibition of ITK, for example, is associated with broader immunologic changes, including skewing towards a Th1 CD4+ phenotype and improved T-cell expansion and fitness [ 15 , 16 , 17 ]. Ibrutinib first came to prominence in studies of CLL, where it was demonstrated to induce high rates of overall response in both previously treated and untreated patients [ 18 , 19 ].…”
Section: Review Of Approved Small Molecule Inhibitorsmentioning
confidence: 99%
“…While this may account for some observed toxicities, these changes may also play a role in therapeutic activity. Inhibition of ITK, for example, is associated with broader immunologic changes, including skewing towards a Th1 CD4+ phenotype and improved T-cell expansion and fitness [ 15 , 16 , 17 ]. Ibrutinib first came to prominence in studies of CLL, where it was demonstrated to induce high rates of overall response in both previously treated and untreated patients [ 18 , 19 ].…”
Section: Review Of Approved Small Molecule Inhibitorsmentioning
confidence: 99%
“…Accumulating data have demonstrated that ibrutinib can directly inhibit the expression of inhibitory receptors (21,44,50,82,84) and reduce the number of terminally differentiated T cells, such as TLTA, Texh, T EM , and T EMRA cells (79, 84) but remain naïve T cells (79). Niemann et al found that PD-1 expression significantly decreased at 4 weeks after ibrutinib treatment in CLL patients (34).…”
Section: Naïve T Cells and Terminally Differentiated T Cellsmentioning
confidence: 99%
“…Nevertheless, in CLL patients, CD4 + T cells stimulate CLL cell survival and proliferation by secreting multiple chemokines/cytokines and through direct contact with the CD40 ligand (27,36,94), and CD8 + T cells are persistently activated and expanded within the CLL microenvironment and gradually become pseudo-exhausted (5,50,52), finally resulting in T-cell immune tolerance and the loss of their anti-tumor activity (27), which has been reported to be causative of the poor response to CAR-T cell therapies for CLL patients (95-97). Additionally, due to the damaged structure of effector T cells and the poor antigen presentation function of CLL cells, the formation of immune synapses between T and CLL cells is impaired (84,98).…”
Section: The Effects Of Ibrutinib On T Cell Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is underscored by the observations that proliferating CLL cells in vivo are located close to activated helper T cells [9][10][11] and that in vitro CLL cells virtually never spontaneously divide [12,13] until they are provided with factors produced by helper T cells, such as CD40L, IL21, and IL4 [11,14,15]. Moreover, changes in the T-cell repertoire have been associated with CLL prognosis [14] and are affected by targeted therapy [15,16]. The T cells of patients with CLL also reveal functional differences with those of the healthy population [17], such as the relative sizes of T-cell subsets [18], the presence of specific clonotypes [19], exhausted phenotypes [20], and lower CD40L levels [7].…”
Section: Introductionmentioning
confidence: 99%